(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
Álvaro Pombo (Santander, 1939) became known in the seventies as a poet and author of short stories to garner important awards as a novelist in the following two decades before publishing a second collection of short stories. His first book of short stories, Relatos sobre la falta de sustancia (1977, 1985b), consists of twelve stories that address the problem of the lack of human substance in the anodyne and inconsequential lives of its protagonists. The second, Cuentos reciclados (1997), is a collection of eleven stories of unequal length preceded by a prologue in which the author discusses some pending issues from the first book and explains his idea of ​​recycling with which he tries to provide a certain unity to these new stories. Other stories of his published in newspapers and magazines have not yet reached volumes. Critics have highlighted Pombo’s fable capacity, his proverbial ability to characterize characters through his speech, and the ironic resources of his narrators, and as recurring thematic aspects, the importance of sexuality, religion, and memory has been discussed. they have in all their literary work.